JPure - Purified Java Execution Environment for Controller Networks - Schröder-Preikschat, Wolfgang; et al. (Proc. of the Intern. IFIP WG 10.3/WG 10.5 Workshop on Distributed and Parallel Embedded Systems, 2001)
This paper presents an approach how to make microcontro/lers able to execute Java applications with very small resource consumption compared to existing Java execution environments. The approach is based on the exploitation of the distributed computing power available in distributed controller network. © 2001 by Springer Science+Business Media New York.
UnivIS-Import:2015-04-16:Pub.2001.tech.IMMD.IMMD4.jpurep